2015
DOI: 10.1002/jnr.23540
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α potentiates long‐term potentiation in the rat dentate gyrus after acute hypoxia

Abstract: An inadequate supply of oxygen in the brain may lead to the introduction of an inflammatory response through neuronal and glial cells that can result in neuronal damage. Tumor necrosis factor alpha (TNF-α) is a pro-inflammatory cytokine that is released during acute hypoxia and can have neurotoxic or neuroprotective effects in the brain. Both TNF-α and interleukin-1β (IL-1β) have been shown by a number of research groups to alter synaptic scaling and also to inhibit long-term potentiation (LTP) in the hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Though others have previously shown that TNFα can facilitate LTP in hippocampal slices under certain conditions [ 56 ], consistent with our findings, several earlier studies reported an impairment in LTP induction in both the dentate and the CA1 regions of the hippocampus following exogenous application of pathophysiological quantities of TNFα [ 27 29 ]. These apparent discrepancies may be attributable to several fundamental methodological differences.…”
Section: Discussionsupporting
confidence: 93%
“…Though others have previously shown that TNFα can facilitate LTP in hippocampal slices under certain conditions [ 56 ], consistent with our findings, several earlier studies reported an impairment in LTP induction in both the dentate and the CA1 regions of the hippocampus following exogenous application of pathophysiological quantities of TNFα [ 27 29 ]. These apparent discrepancies may be attributable to several fundamental methodological differences.…”
Section: Discussionsupporting
confidence: 93%
“…There are many factors regulating the magnitude of LTP induced by different parameters such as high frequency stimulation and theta burst stimulation [ 101 ] ( Figure 3 ). Recently, we have shown that the stimulation parameters used to induce LTP may have an influence on TNF-α’s ability to inhibit LTP [ 102 ]. TNF-α has no inhibitory effect on LTP when induced with prolonged high frequency stimulation (HFS) whereas full inhibition was observed when LTP was induced by theta burst stimulation (TBS).…”
Section: Tnf-α and Synaptic Plasticitymentioning
confidence: 99%
“…All these effects by TNF-α result in the increase in the concentration of glutamate in the synaptic cleft, which may have an influence on the magnitude of LTP post-hypoxia. Using a robust LTP-inducing stimulus protocol we have been able to demonstrate a significant enhancing effect of TNF-α on LTP post hypoxia but only in the dentate gyrus of the hippocampus [ 102 ]. In the presence of DMOG (a non-specific PHD inhibitor) this enhancement of LTP was still evident perhaps indicating a novel HIF/PHD-independent effect of TNF-α [ 102 ].…”
Section: Tnf-α Hypoxia and Synaptic Plasticitymentioning
confidence: 99%
“…These results suggest an important role for TNF-a signaling in modulation of EphB2 expression. TNF-a has been shown to be involved in synaptic plasticity (Marchetti et al, 2004;Pickering et al, 2005;Belarbi et al, 2012;Wall et al, 2015), but a connection to EphB2 has not yet been established in human neurons.…”
Section: Journal Of Cellular Physiology T N F -A a C T I V A T I O N mentioning
confidence: 99%